Tests on full-scale and static analysis models of the wood-framed building stucture horizontaly loaded - Malesza, Jaroslaw; Miedzialowski, Czeslaw; Ustinovichius, Leonas (Journal of Civil Engineering and Management, 2017)
This paper focuses on development of the high energy saving timber building and ecological technology protecting environment in civil engineering. Wood framed with sheathing, large panel structures became more popular building constructions in Poland last decade. Experimental tests and numerical analysis of panels and complete wood framed building have been taken into account. Typical two-story residential building was selected for test. Test of three dimensional (3D) whole building was conducted on the base of experimental investigations results of large panel similar to those used in building structure. Also adequate tests of materials and connections were accompanying of the whole structure investigations. Obtained results were adopted in numerical models elaborated for wall and floor panels and in 3D model of whole building. Load -displacements characteristics were acquired from tests and numerical models. The displacements computed from 3D numerical model were 10–20% higher than from experiment. Experimentally ob-tained lower displacements than those from analytical analysis are resulted from higher stiffness of wall system due to diaphragms interconnections, their common interaction and three-dimensional character of building structure. Presented research analyzed method of computation of internal forces in building as well in the range of engineering methods in the form of rigid beam scheme up to the advanced methods using 3D spatial model adopting FEM.